Optimizing Lower Limb Power in Taekwondo Players: A Training Intervention Study - Muhammad Shaheer Ali; Naseem Ullah; Saqlain Ali (`, 2025)
This study investigated the effectiveness of plyometric training for peak lower limb power and agility in Taekwondo athletes. Thirty male provincial-level Taekwondo athletes from the age group of 17–24 years of Khyber Pakhtunkhwa province having a minimum training history of three years were randomly assigned into experimental (n = 15) and control (n = 15) groups. True experimental design with pre- and post-test measurement was adopted. The power of the lower limbs was measured using the Vertical Jump Test, while agility was measured using the Agility T-Test. The experimental group underwent eight weeks of plyometric training, two times weekly, in the form of progressive drills such as box jumps, tuck jumps, hurdle jumps, and reactive agility drills, while the control group underwent normal training. Data were contrasted using paired and independent sample t-tests in SPSS (v26) at p < 0.05 level of significance. Outcomes showed improvements from pre- to post-test in both groups to be significant, yet the experimental group showed significantly larger improvements in both lower limb power and agility with larger mean differences and high statistical significance. Baseline comparisons prohibited any initial differences, while post-test analyses revealed strongly significant advantages for the experimental group. These findings are valuable evidence to reject the null hypothesis and conclude plyometric training is effective as a treatment for enhancing explosive power and agility among Taekwondo athletes. The study sets forth the applied use of the incorporation of plyometric drills into Taekwondo conditioning programs to maximize competitive performance and proposes future research on the long-term effects, cross-gender application, and integration of other forms of conditioning. Keywords: Plyometric training, lower limb power, agility, Taekwondo, athletic performance, experimental study, conditioning program